Desegregation, resegregation and centre/periphery relationships in Durban - (:unkn) unknown (My University, 2002)
What processes are operating to bring about these changes, almost all agree that there has been "a pronounced resurgence in inequality, a widening gap between the rich and the poor" which "remains the most challenging public and political finding of the literature on urban restructuring and needs to be seen as an integral part of post-modern urbanism and postmodern urban politics" (Soja, 2001, 44). This inequality has clear spatial impacts. "Given a high and rising level of urbanization, growing income inequality, and rising class segregation, an increase in the geographic concentration of affluence and poverty is all but inevitable. These spatial processes are magnified, however, when they occur in a group that is also segregated on the basis of an ascribed characteristic such as race" (Massey, 1996, cited in Cooke, 1999).
Keywords: African Research